Impactful Indigenous Technical Knowledge (ITK) for sustainable agriculture - BHAN, SURAJ; BHARTI, V.K; ., MEETALI; ., DEEPSHIKHA; BHARTI, SANDEEP; BHARTI, SANJAY (Journal of Soil and Water Conservation, 2020)
The advent of the concept of sustainable agriculture in late eighties in Indian agricultural scenario has evoked interest on indigenous technical knowledge (ITK) that has the element of use of natural products to solve the problems pertaining to agriculture and allied activities. Indian farmers, over centuries, have learnt to grow food and to survive in difficult environments, where the rich tradition of ITK has been interwoven with the agricultural practices followed by them. Indigenous Technical Knowledge (ITKs) are treasure troves of ancient wisdom, beliefs and traditional knowledge passed on from generation to generation for preservation, effective utilization and conservation of natural resources, soil, plant and other organisms. It is a well-known fact that India has a charitable and glorious heritage of past, both in richness and variety in performing agricultural and allied practices. ITKs are based on experience, often tested over a long period of use, adapted to local culture and environment, dynamic and changing, and lay emphasis on minimizing the risks rather than maximizing the profits. It has the element of use of natural products to solve the problems pertaining to agriculture and allied activities. But, despite these, the ITK at the farmer’s level receive less recognition by the organizations. Also the propriety rights on ITK have often been ignored. It is so, because of the key actors are not working closely with each other. Hence, there is an urgent need to have institutional reforms especially for better coordination, convergence and efficiency in action in recognizing and encouraging the scientific talents behind such grass root level ITKs and widely sharing benefits accrued from such ITKs across the country. The objective of this paper is mainly to get thorough understanding of the role of institutions in promotion and commercialization of ITKs and suggesting effective strategies in up scaling and out scaling of ITKs.